Wish versus Worry: Ownership Effects on Motivated Judgment. (April 2013) - Dai, Xianchi; Hsee, Christopher K.
How do consumers' needs and motivations influence their perceptions of external objects? For example, do hungry people perceive a cake to be larger or smaller than do satiated people? According to the New Look psychology literature, the answer is invariably "larger." However, in this article, the authors demonstrate that the answer is more complex depending on whether the object belongs to the perceiver. If the cake does not belong to the perceiver, she will perceive it to be larger if she is hungry than if she is satiated. In contrast, if the cake already belongs to her, she will perceive it to be smaller if she is hungry than if she is satiated. The authors propose a two-process (wishful thinking vs. worryful thinking) hypothesis to explain the finding and discuss its theoretical and marketing implications.